Strategies Used by Islamic Religious Education Teachers to Instill a Spirit of Religious Moderation in Generation Z - Abdul Hamid; Aca Syathybie (Pelopor Publikasi Akademika, 2026)
This study explores the role of Islamic Religious Education teachers in strengthening religious moderation among Generation Z in response to the growing influence of digital media on students' religious understanding. The increasing circulation of religious content through social media platforms has raised concerns regarding the spread of intolerant and exclusive interpretations, necessitating educational intervention to maintain balanced religious perspectives. The purpose of this research is to analyse the strategies employed by Islamic Religious Education teachers in instilling moderation values in students within school environments. The research employs a qualitative case study approach involving Islamic Religious Education teachers, school principals, and Generation Z students as informants. Data were collected through observation, in-depth interviews, and documentation, and analysed using the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing. The findings reveal that teachers implement multiple integrated strategies, including role modelling, the integration of moderation values into learning materials, the strengthening of digital religious literacy, dialogical learning methods, and the cultivation of a moderate school culture. The results indicate that teacher exemplification is the most influential factor in shaping students' moderate attitudes, followed by interactive and contextual learning practices. Strengthening digital literacy also plays a crucial role in improving students' ability to critically evaluate online religious information. In conclusion, the combined implementation of pedagogical, digital, and cultural strategies effectively fosters tolerant, inclusive, and nationally oriented religious character among Generation Z students.